Algumas metodologias de avaliação para pavimentos de baixo volume de trafego - Teixeira, Jonas Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This work has as objective, show and compares some of several evaluation methods of pavements, based in the rules and researches realized by another authors, with focus on low traffic volume pavements, which are generally more economic flexible pavements subjected to low loads. Were addressed structure evaluation methods and superficial evaluation methods applied to that kind of pavement, exposing of clearly the procedures to be performed, the advantages and disadvantages, as well the results obtained in the execution of each one of these. This theme was chosen by the widespread use of this type of pavement in the road network of the country and the fact that there is no still a culture of the practical of evaluation nor technical knowledge on the part of municipal governments that are usually responsible for these roads. This study also aims to guide the process of maintenance preventive or recuperative, as they are often made improvements that do not actually solve the real problem of the roads
Keywords: Pavimento de concreto asfaltico; Estradas - Conservação e restauração